Harnessing Nuclear Magnetic Resonance Spectroscopy to Decipher Structure and Dynamics of Clathrate Hydrates in Confinement: A Perspective - Houlleberghs, Maarten; Radhakrishnan, Sambhu; Chandran, C. Vinod; Morais, Alysson F.; Martens, Johan A.; Breynaert, Eric (Molecules (Basel, Switzerland), 2024)
This perspective outlines recent developments in the field of NMR spectroscopy, enabling new opportunities for in situ studies on bulk and confined clathrate hydrates. These hydrates are crystalline ice-like materials, built up from hydrogen-bonded water molecules, forming cages occluding non-polar gaseous guest molecules, including CH4, CO2 and even H2 and He gas. In nature, they are found in low-temperature and high-pressure conditions. Synthetic confined versions hold immense potential for energy storage and transportation, as well as for carbon capture and storage. Using previous studies, this report highlights static and magic angle spinning NMR hardware and strategies enabling the study of clathrate hydrate formation in situ, in bulk and in nano-confinement. The information obtained from such studies includes phase identification, dynamics, gas exchange processes, mechanistic studies and the molecular-level elucidation of the interactions between water, guest molecules and confining interfaces.